Security of Wireless Sensor Nodes - Msekh, Alya’a Abdulrazzak; Kadhim, Jamal Mohamed (Iraqi Journal of Science, 2020)
Due to the large-scale development in satellite and network communication technologies, there is a significant demand for preserving the secure storage and transmission of the data over the internet and shared network environments. New challenges appeared that are related to the protection of critical and sensitive datafrom illegal usage and unauthorized access. In this paper, we address the issues described above and develop new techniques to eliminate the associated problems. To achieve this, we propose a design of a new sensor node for tracking the location of cars and collecting all information and all visited locations by cars, followed byencryption in a sensor node and saving in the database. A microcontroller of Arduino esp8266 Node MCU board and a GPS module are used. The cryptography uses the chaos-based symmetric-key encryption technique for data. This scheme utilizes a chaotic map (Hénon map) for robustness and security of data. The key sensitivity can be performed by statistical experiments to determine the safety, reliability, and speed of the algorithm. The proposed algorithm presents several exciting features, such as a high level of security, sufficient saving of the energy of the sensor network, and an acceptable encryption speed compared to Advanced Encryption Standard (AES) and Data Encryption Standard (DES).